An Analysis of Rotational Line Mating Using Computer Simulation - Szőke, Szilvia; Komlósi, István (Acta Agraria Debreceniensis, 2005)
In a simulation examination, we analyzed the effect of the family size and the rate of pairing on the survival of rare genes, to keep the level of variation of the genepool and to avoid the loss of alleles.The population size was 360 animals. In the simulation, we calculated on the basis of a discrete population. We placed the 360 animals into different clusters, with 3 types of frequencies of alleles and 3 types of groups. We assumed 2, 3 or 4 alleles in 8 loci. We generated 15 generations using the same mating and selection system used in practise. The simulation was written with Scilab 2.7.2 software, and evaluated with SPSS software.There were significant changes in the effect of family size on the genetic variation in the following cases: when the base population had the same gene frequencies in all loci, and when the gene frequencies were between 0.125-0.75. In these cases, we found that the smaller families (10 animals/cluster) were better than the larger families (30 or 90 animals/cluster). The first generation where there accured a loss of alleles was averagely earliest in larger families (90 animal/cluster). This average was 3.37 generations. When we are searched the effects of the different rates of pairing we found those cases most favourable when the ratio of males and females was 1:2 or 1:4 as compared to 1:9. The first generation where there was a loss of alleles was averagely earliest at the ratio of pairing male and females of 1:9 (the mean was 3.05 generations) when the frequency of the rarest allele was 0.0069.The recently introduced rotating-random mating system is an eligible method for small populations for the preservation of genes.